Effect of Exercise Therapy, Electrical Therapy, and Heat Therapy on Hamstring Injury Pain Levels of SPFA Athlete - Kurnia, Fandy Ahmad; Setiowati, Anies (Universitas Negeri Semarang, 2023)
Hamstring muscle injuries often occur in athletes, especially in soccer, athletes who are injured on average experience pain in their muscles. Therefore, proper treatment can speed up the rehabilitation process for hamstring muscle injuries in the form of exercise therapy, electrical therapy, and heat therapy. This type of research is a quantitative experiment. Data collection techniques using Numeric Rating Scale sheet. Using purposive sampling which collected 30 people, namely soccer athletes from Safin Pati Football Academy aged 12-16 years. The data analysis technique used nonparametric statistical tests because the data distribution was not normal, namely using the Wilcoxon test. The results of this study obtained the lowest value for the calculation of the Numeric Rating Scale pretest was 3 and the highest value was 6 with an average of 4.7. The lowest value of the post-test Numeric Rating Scale calculation is 1 and the highest value is 3 with an average of 1.8. In the analysis test with the Wilcoxon test, a P-value of 0.000 was obtained. It can be said that p < 0.05 which means that there is a difference in meaning between the calculation of the Numeric Rating Scale pretest and posttest or Ha is accepted. Conclusions from the results of research and discussion, it can be said that exercise therapy, electrical therapy, and heat therapy affect hamstring injuries in soccer athletes at the Safin Pati Football Academy.